Estrategias didácticas desde la tecnología para la mejora del proceso de enseñanza-aprendizaje de estudiantes del subnivel básica elemental. - Morán Castro, Estefanía Vanexsa (2025)
The overall objective of this research was to establish teaching strategies based on technology to improve the teaching and learning process of language and literature among students in the elementary level of the Escuela de Educación Básica “Región Litoral” (Litoral Region Elementary School). This study was conducted using a qualitative approach aimed at understanding pedagogical processes based on the experiences of teachers and students. The design is phenomenological, because it analyzed, from direct experience, how teachers implement or integrate technology in the classroom. The population consists of a total of 12 teachers and 241 students from the “Región Litoral” Basic Education School, and the sample consists of 60 second-grade students from parallel classes ‘A’ and “B” of Basic General Education. The methods of information gathering included observations and interviews to characterize the teaching process and understand the perceptions and difficulties related to the use of technology. The results show that students must continue to strengthen their literacy skills and improve their participation in technological tools. In addition, teachers should continue to integrate various interactive activities using technology into their classes to make their activities interactive and motivating. It is concluded that the proper integration of technological resources in the classroom promotes a more interactive and personalized teaching approach that is in line with contemporary challenges. It is important to remember that each student has a different learning pace, which is why teachers need to integrate a variety of technological teaching methods for their students.